2009
DOI: 10.1161/strokeaha.109.562769
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care International Normalized Ratio Testing Accelerates Thrombolysis in Patients With Acute Ischemic Stroke Using Oral Anticoagulants

Abstract: Background and Purpose-Thrombolysis in patients using oral anticoagulants (OAC) and in patients for whom information on OAC status is not available is frequently delayed because the standard coagulation analysis procedure in central laboratories (CL) is time-consuming. By using point-of-care (POC) coagumeters, international normalized ratio (INR) values can be measured immediately at the bedside. The accuracy and effectiveness of POC devices for emergency management in acute ischemic stroke has not been tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 26 publications
4
71
0
2
Order By: Relevance
“…In the warfarin group, INR was assessed by a point-of-care coagulometer (Coaguchek XS, Roche, Penzberg, Germany) 19 before surgery to assure effective systemic anticoagulation in each individual animal (INR 2 to 3; Supplementary Information).…”
Section: Assessment Of Coagulation Statusmentioning
confidence: 99%
“…In the warfarin group, INR was assessed by a point-of-care coagulometer (Coaguchek XS, Roche, Penzberg, Germany) 19 before surgery to assure effective systemic anticoagulation in each individual animal (INR 2 to 3; Supplementary Information).…”
Section: Assessment Of Coagulation Statusmentioning
confidence: 99%
“…The current study identified an excellent correlation between the POC and the SCA INR, similar to that shown in previous studies. This finding demonstrates that the POC device is accurate, reliable and comparable to the SCA INR for use in patients with long-term use of oral anticoagulants 4,5,8,10 . POC could be useful in several situations, as patients without access to a medical laboratory could achieve better control with OAT 6 ; and in patients with acute IS who are within the therapeutic window for thrombolysis, evaluating INR using POC could be performed in the pre-hospital emergency medical service or in the hospital emergency room, reducing the time to treatment.…”
Section: Discussionmentioning
confidence: 57%
“…In a previous study, POC INR was precise for emergency management of thrombolysis in patients with acute IS and reduced the interval to INR results. The time gain using the POC compared to INR was 28 minutes 8 . This delay could compromised the effectiveness of thrombolysis in acute stroke care.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of thrombolysis in acute cerebrovascular accidents strongly depends on the interval between the onset of symptoms and administration of thrombolytic therapy [12]. Rizos et al [13] observed significant and clinically relevant time to onset of thrombolytic therapy, 28 ± 12 minutes with the use of INR-POCT.…”
Section: The Inr-poct Advantagesmentioning
confidence: 99%